The Utilization of Information Technology to Support Organizational Performance at SMA Hang Tuah 5 Sidoarjo - Lilik Handayani; Sabariah Sabariah (Journal of Educational Sciences, 2026)
The development of information technology in the digital era encourages schools to build a more effective, adaptive, and integrated organizational management system. The use of information technology has an important role in supporting communication, administration, coordination, and organizational effectiveness in educational institutions. This study aims to analyze the use of information technology and its contribution in supporting the effectiveness of organizational performance at SMA Hang Tuah 5 Sidoarjo, including the obstacles faced and optimization efforts carried out by the school. This study uses a qualitative approach involving five teachers who are members of the curriculum team and selected through convenience sampling techniques. The results show that information technology is used through Canva, smart board, IFP, Google Workspace, Moodle LMS, and WhatsApp groups to support administration, communication, coordination, and collaboration in school organizations. However, several obstacles were found, such as differences in technological understanding, limited personal work facilities, and delays in administrative collection by some teachers. The school makes various efforts through continuous coordination, structured division of tasks, teacher mentoring, periodic monitoring, and routine evaluation of work programs. The use of information technology contributes to increasing the effectiveness and adaptability of school organizational performance in the digital era.